2002
DOI: 10.1080/02331880213192
|View full text |Cite
|
Sign up to set email alerts
|

Markov Chain Markov Field dynamics: Models and statistics

Abstract: This study deals with time dynamics of Markov fields defined on a finite set of sites with state space E, focussing on Markov Chain Markov Field (MCMF) evolution. Such a model is characterized by two families of potentials: the instantaneous interaction potentials, and the time delay potentials. Four models are specified: auto-exponential dynamics (E = R + ), auto-normal dynamics (E = R), auto-Poissonian dynamics (E = N) and auto-logistic dynamics (E qualitative and finite). Sufficient conditions ensuring ergo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(24 citation statements)
references
References 23 publications
(14 reference statements)
0
24
0
Order By: Relevance
“…Let Ω = E S denote the configuration space, i.e., the state space of the entire network. Let X i (t) ∈ E be the state of station i at time t, and X(t) = {X i (t)} i∈S ∈ Ω be the configuration, or the state of the network, at time t. We are interested in MAC protocols for which X = {X(t)} t∈N is a Markov Chain of Markov Field (MCMF) [6], i.e., a process for which…”
Section: Markov Chain Of Markov Fields (Mcmf) Model For Mac Protmentioning
confidence: 99%
See 4 more Smart Citations
“…Let Ω = E S denote the configuration space, i.e., the state space of the entire network. Let X i (t) ∈ E be the state of station i at time t, and X(t) = {X i (t)} i∈S ∈ Ω be the configuration, or the state of the network, at time t. We are interested in MAC protocols for which X = {X(t)} t∈N is a Markov Chain of Markov Field (MCMF) [6], i.e., a process for which…”
Section: Markov Chain Of Markov Fields (Mcmf) Model For Mac Protmentioning
confidence: 99%
“…In [6] it is shown that a sufficient condition for this to occur is that the Markov chain is time-reversible and the transition probability is synchronous. We consider these two properties in the following.…”
Section: Markov Stationary Behavior Of Mcmfmentioning
confidence: 99%
See 3 more Smart Citations